Correction: Demographic and Clinico-Epidemiological Features of Dengue Fever in Faisalabad, Pakistan. - Eun Jeong Yu; Eun-A Park; Seung-Ah Choe; Kyung-Ah Lee; You Shin Kim (PLoS ONE, 2023)
[This corrects the article DOI: 10.1371/journal.pone.0267652.].